Stock Market Reactions to Customer Service Outsourcing in Manufacturing Firms - Eggert, A; Böhm, E; Cramer, C (2015 AMA Winter Marketing Educators’ Conference Proceedings)

Service transition versus service infusion: Different pathways to success for service-oriented manufacturers? - Kanuri, V; Münkhoff, E; Scheer, L. K (ISBM 2014 Academic Conference)

Selling value in business markets: Why a powerful idea often fails - Eggert, A; Haas, A; Terho, H; Ulaga, W; Münkhoff, E (ISBM 2014 Academic Conference)

The corporate marketing department - Between value and vanish - Ritter, T; Eggert, A; Münkhoff, E; Ulaga, W (ISBM 2014 Academic Conference)

Service transition: A viable option for manufacturing companies with declining financial performance? - Eggert, A; Münkhoff, E; Thiesbrummel, C (Proceedings of the 43rd European Marketing Academy (EMAC) Conference)

Overcoming Roadblocks to Value-Based Selling: Aligning Organizational Support With Sales Force Activities - Terho, H; Eggert, A; Ulaga, W; Haas, A (2014 AMA Winter Marketing Educators’ Proceedings)

Towards a Simulation-based Approach for Evaluating Business Models for the Electric Vehicle Market

Linguistic Consistency of Goal Models - Pittke, Fabian; Nagel, Benjamin; Engels, Gregor; Mendling, Jan (Proceedings of the 19th International EMMSAD Conference)

Breathing Life into Situational Software Engineering Methods - Fazal-Baqaie, Masud; Gerth, Christian; Engels, Gregor (In Proceedings of the 15th International Conference of Product Focused Software Development and Process Improvement (PROFES 2014))
Software engineering methods are used to prescribe and coordinate the tasks necessary to plan, build, deliver, and maintain software. There is a broad consensus that there is no one-size-fits-all method and that, e.g., agile and plan-driven approaches have to be mixed sometimes, based on the context of a project. Creating these so-called situational methods and assuring that they cover all necessary details consistently is a challenge. There is also the challenge for the project teams to follow methods as prescribed by the method engineer. Our approach supports the creation of consistent situational methods from a repository of pre-existing building blocks. Moreover, we present means to enact these methods with standard BPEL/BPEL4People workflow engines, automating the coordination of tasks and providing guidance for them.

Agile Entwicklung mit On- und Offshore-Partnern – Methodenverbesserung in der Praxis - Fazal-Baqaie, Masud; Sauer, Stefan; Heuft, Torsten (Proceedings of Projektmanagement und Vorgehensmodelle 2014)
Agile Softwareentwicklungsmethoden erfreuen sich einer steigenden Verbreitung, versprechen sie doch risiko-getrie-ben und leichtgewichtig auch bei sich verändernden Anforderungen gute Ergebnisse zu erzielen. Viele Unternehmen stehen jedoch vor der Herausforderung, agile Prinzipien mit den Gegebenheiten im Unterneh-men zu vereinbaren, z.B. mit den internen Prozessen und organisatori-schen Gegebenheiten. Ein besonders herausforderndes Beispiel ist die Softwareentwicklung in Kooperation mit Offshore-Partnern. Die Auto-ren berichten aus einem laufenden Methodenverbesserungsprojekt für ein Unternehmen der Finanzbranche, das für die Softwareentwicklung mit On- und Offshore-Partnern kooperiert. Anders als bisher soll der indischen Offshore-Partner in naher Zukunft große Softwaressysteme federführend implementieren. Dabei sollen projektindividuell auch Onshore-Partner eingebunden werden. Der Beitrag stellt den systema-tischen Ansatz für die inkrementelle Methodenverbesserung vor, mit dem Varianten einer möglichst agilen Methode definiert werden sollen, die sowohl im Projektumfeld als auch im operativen Tagesgeschäft ef-fektiv und effizient eingesetzt werden können. Die Autoren fassen au-ßerdem die im Rahmen von Interviews erhobenen, bisherigen Erfah-rungen in der Zusammenarbeit mit dem Offshore-Partner zusammen, die für die Methode berücksichtigt werden müssen.

Configuration of Specification Language and Matching for Services in On-The-Fly Computing - Arifulina, Svetlana; Christin Platenius, Marie; Gerth, Christian; Becker, Steffen; Engels, Gregor; Schäfer, Wilhelm

A Decision Support System for IT Security Incident Management - Rauchecker, Gerhard; Yasasin, Emrah; Schryen, Guido (11th International Conference on Trust, Privacy, and Security in Digital Business (TRUSTBUS))

Model-based Decision Support in Manufacturing and Service Networks - Fink, Andreas; Kliewer, Natalia; Mattfeld, Dirk; Mönch, Lars; Rothlauf, Franz; Schryen, Guido; Suhl, Leena; Voß, Stefan (Business & Information Systems Engineering (BISE))

Modellbasierte Entscheidungsunterstützung in Produktions- und Service-Netzwerken - Fink, Andreas; Kliewer, Natalia; Mattfeld, Dirk; Mönch, Lars; Rothlauf, Franz; Schryen, Guido; Suhl, Lena; Voß, Stefan (Wirtschaftsinformatik)

Spillover Effects of Service Failures in Coalition Loyalty Programs: The Buffering Effect of Special Treatment Benefits. - Schumann, Jan H; Wünderlich, Nancy; Evanschitzky, Heiner (Journal of Retailing)
Coalition loyalty programs are on the rise, yet few studies investigate the impact of service failures in such programs. Using data from a retail context, the authors show that a program partner deemed responsible for a service failure suffers negative customer responses. However, customers’ perceptions of the benefits of the coalition loyalty program buffer these consequences. Perhaps most importantly, when customers perceive the program's special treatment benefits as low, direct and indirect spillover effects occur, such that a service failure by one program partner has a negative effect on customer loyalty toward the program itself.
Keywords: Service failure; Spillover effects; Buffering effect; Coalition loyalty program

A software product line for static analyses: The OPAL framework - Eichberg, Michael; Hermann, Ben (Proceedings of the 3rd ACM SIGPLAN International Workshop on the State of the Art in Java Program Analysis - SOAP '14)

FlowTwist: efficient context-sensitive inside-out taint analysis for large codebases - Lerch, Johannes; Hermann, Ben; Bodden, Eric; Mezini, Mira (Proceedings of the 22nd ACM SIGSOFT International Symposium on Foundations of Software Engineering - FSE 2014)

Model-Based User Interface Development for Adaptive Self-Service Systems - Yigitbas, Enes; Fischer, Holger Gerhard; Sauer, Stefan (Design, User Experience, and Usability. Theories, Methods, and Tools for Designing the User Experience - Third International Conference, DUXU 2014, Held as Part of HCI International 2014, Heraklion, Crete, Greece, June 22-27, 2014, Proceedings, Part I)

Model-Based Development of Adaptive UIs for Multi-channel Self-service Systems - Yigitbas, Enes; Fischer, Holger Gerhard; Kern, Thomas; Paelke, Volker (Human-Centered Software Engineering - 5th IFIP WG 13.2 International Conference, HCSE 2014, Paderborn, Germany, September 16-18, 2014. Proceedings)

Flexible & Adaptive UIs for Self-Service Systems - Yigitbas, Enes; Sauer, Stefan (Mensch & Computer 2014 - Workshopband, 14. Fachübergreifende Konferenz für Interaktive und Kooperative Medien - Interaktiv unterwegs - Freiräume gestalten, 31. August - 3. September 2014, München, Germany)